2008
DOI: 10.1002/anie.200703103
|View full text |Cite
|
Sign up to set email alerts
|

Practical Implications of Boron‐to‐Zinc Transmetalation for the Catalytic Asymmetric Arylation of Aldehydes

Abstract: Faster than believed: Transmetalation from aryl boronic acids and triaryl boroxines to diethylzinc takes place within minutes following a two‐step, low‐energy pathway (see picture), according to density functional calculations and reaction microcalorimetry measurements. The experimental conditions for a practical, atom‐economical, and highly enantioselective catalytic arylation of a variety of aldehydes have been developed from these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…Dimethyl (polyethylene glycol) (DiMPEG, 10 mol %, MW∼2,000) was used as an additive to inhibit the background reaction caused by achiral Lewis acidic ZnPh 2 or ZnBr 2 43,49,50. Further study and optimization by the groups of Pericàs and Magnus significantly reduced the transmetallation time 51,52. Braga demonstrated that the acceleration could be achieved by microwave irradiation 53.…”
Section: Introductionmentioning
confidence: 99%
“…Dimethyl (polyethylene glycol) (DiMPEG, 10 mol %, MW∼2,000) was used as an additive to inhibit the background reaction caused by achiral Lewis acidic ZnPh 2 or ZnBr 2 43,49,50. Further study and optimization by the groups of Pericàs and Magnus significantly reduced the transmetallation time 51,52. Braga demonstrated that the acceleration could be achieved by microwave irradiation 53.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylation/cyclopropanation of α-phenyl enals Scheme 3. One-pot method for the synthesis of 1,2,3-substituted cyclopropanes from enals Initially, the phenyl(ethyl)zinc species was generated in situ through transmetallation between triphenylboroxin and diethylzinc in toluene at 60ºC for 30 min, 21 and subsequently the addition of the aldehyde to the reaction mixture in the previously reported optimal conditions 18b was carried out. Next, instead of quenching the zinc alkoxide, the cyclopropanation of the double bound was performed at room temperature in light exclusion without the need of removing the boron species.…”
Section: Resultsmentioning
confidence: 99%
“…In 2008 we published that triarylboroxins undergo a scrambling process with Et 2 Zn that generates in situ the corresponding arylzinc species. This strategy greatly simplified the arylation of aldehydes, avoiding the use of expensive and difficult to prepare diarylzinc derivatives . Hence, we reasoned that integrating this approach with the knowledge acquired on the previous work with ligand 25 would allow to carry out the enantioselective continuous arylation of aldehydes with triarylboroxins as the ultimate source of aryl groups.…”
Section: Immobilized Ligands and Metal‐based Catalysts For Work In Flowmentioning
confidence: 99%